Validation of Lumped Mass Lateral Cantilever Shaft Vibration Simulation on Fixed-Pitch Vertical-Axis Ocean Current Turbine - Hantoro, R. Hantoro; Utama, I. K. A. P. Utama; Sulisetyono, A. Sulisetyono; Erwandi, Erwandi (IPTEK The Journal for Technology and Science, 2010)
Research on the emergence of force fluctuations and shaft vibration responses of ocean currents turbine generator become a serious concern to the researchers. This paper was conducted with the aim of investigation into the characteristics of lateral shaft vibration of a fixed-pitch vertical-axis ocean current turbine (VAOCT). The work was carried out numerically and experimentally using tank test. A cantilever type of shaft has been used and modeled using finite element method, and simulated using lumped mass matrix to obtain the vibration characteristics and responses. Variations of incoming fluid velocity and the corresponding rotation velocity (rpm) of VAOCT were used to identify the pattern of lateral displacement responses. Analysis of displacement responses at all nodes in x and y-direction at the same time was carried out. The presents of displacement shapes recognized have close agreement to the 1st mode shape. Potential problems on the tip of shaft obviously due to half of the force of turbine received concentrated at cantilever tip. The pattern of vibration responses from the test data shows suitable with simulation. Periodic pattern responses resulted from simulation and experiment at the validated node produce the minimum displacement error of 14% at Var-3 (U=1 m/s) and maximum of 24% at Var-2 (U=0.9 m/s).